2018
DOI: 10.1186/s40645-018-0231-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in isotopic composition and the origin of precipitation over Bangladesh

Abstract: Water isotopic composition (δ 18 O and δD) in terrestrial proxies of past precipitation enable us to better understand and interpret variation in the Indian Summer Monsoon (ISM). Previous studies have suggested that the origin of precipitation is an important factor controlling the isotopic composition of precipitation around the Indian subcontinent; however, it is difficult to quantify using the Lagrangian approach because the approach does not satisfy the assumption of an adiabatic process over a convective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 66 publications
4
21
0
Order By: Relevance
“…Teleconnection analysis of Bangladesh's seasonal rains 21 correlated with the post-monsoon rain in the entire country, and the negative correlation mostly became significant in the recent epoch. Significant influence of ENSO on the post-monsoon rain in Bangladesh mostly agrees with the findings of [66], who showed that the Pacific Ocean, the BoB, and land surface were the main moisture sources inducing the post-monsoon rain in the country.…”
Section: Post-monsoonsupporting
confidence: 87%
“…Teleconnection analysis of Bangladesh's seasonal rains 21 correlated with the post-monsoon rain in the entire country, and the negative correlation mostly became significant in the recent epoch. Significant influence of ENSO on the post-monsoon rain in Bangladesh mostly agrees with the findings of [66], who showed that the Pacific Ocean, the BoB, and land surface were the main moisture sources inducing the post-monsoon rain in the country.…”
Section: Post-monsoonsupporting
confidence: 87%
“…More negative δ 18 O and δ 2 H values are usually found at higher elevations and in the continental region than the low‐lying and coastal areas, likely due to the altitude effect and continental effect (Gonfiantini et al, 2001), respectively. In addition to the effects mentioned above, extremely negative values are also correlated with deep convection, particularly in tropical regions (Ahmed et al, 2020; Tanoue et al, 2018).…”
Section: Introductionmentioning
confidence: 95%
“…These sites are Port Blair in the Andaman Islands (data available: 2012-2018; [26,[28][29][30]), Minicoy Island in the Arabian Sea (2015-2018; [31]); Kolkata in east India (2015-2018; [26]); Darjeeling (2013-2018) and Tezpur in northeast India (2016-2018; [26]); Ahmedabad (2007) [25] and Pune in west India (2014-2018; [32,33]), Bandipora in north India (July-2016 to June-2018; [34]) and Kozhikode in south India [22]. Precipitation isotope data of a few sites in Bangladesh have also been used [29,35]. Figure 1 shows the precipitation sampling sites and the core monsoon zone of India (shaded).…”
Section: Methodsmentioning
confidence: 99%
“…This process is also likely to contribute to yielding a relatively high K value for the monsoon season. The post-monsoon season, on the other hand, gets moisture from multiple sources [35], which also makes the corresponding distribution pattern skewed in the negative direction.…”
Section: Northeast India and Bangladeshmentioning
confidence: 99%